2018
DOI: 10.1111/pce.13210
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Seq-based high resolution gene expression atlas of chickpea (Cicer arietinum L.) reveals dynamic spatio-temporal changes associated with growth and development

Abstract: Chickpea is one of the world's largest cultivated food legumes and is an excellent source of high-quality protein to the human diet. Plant growth and development are controlled by programmed expression of a suite of genes at the given time, stage, and tissue. Understanding how the underlying genome sequence translates into specific plant phenotypes at key developmental stages, information on gene expression patterns is crucial. Here, we present a comprehensive Cicer arietinum Gene Expression Atlas (CaGEA) acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 69 publications
2
67
1
Order By: Relevance
“…This study identified 3190 novel genes, thus exhibiting the potential of RNA‐seq in the discovery of novel genes in the sequenced genomes as well. Similar results were also observed in other studies in chickpea (Garg et al ., ; Kudapa et al ., ). A total of 6767 genes showed differential expression pattern in different genotypes under different conditions at different time points.…”
Section: Discussionmentioning
confidence: 97%
“…This study identified 3190 novel genes, thus exhibiting the potential of RNA‐seq in the discovery of novel genes in the sequenced genomes as well. Similar results were also observed in other studies in chickpea (Garg et al ., ; Kudapa et al ., ). A total of 6767 genes showed differential expression pattern in different genotypes under different conditions at different time points.…”
Section: Discussionmentioning
confidence: 97%
“…Current advances in high throughput transcriptome sequencing technologies, especially RNA sequencing (RNA-seq), have provided novel insights into the molecular basis of drought tolerance by revealing the comprehensive landscape of divergent gene expression and their complex regulatory networks at various developmental stages at the transcriptional level (Garg et al, 2016;Kudapa et al, 2018). Before the advent of RNA-seq, microarray-based technologies and expressed sequenced tags (ESTs) were exclusively devoted to elucidating the preliminary function of various drought-stress-responsive genes/differentially expressed genes (DEGs) in chickpea (Mantri et al, 2007;Varshney et al, 2009;Deokar et al, 2011).…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%
“…Furthermore, to identify the precise role of various candidate genes identified in the "hotspot QTL" region pinpointed by Kale et al (2015) at the gene expression level, RNA-seq based global gene expression analysis revealed differential expression of nine candidate genes under water stress (Kudapa et al, 2018). Four genes namely E3 ubiquitin-protein ligase, LRX 2, kinase i n t e r a c t i n g ( K I P 1l i k e ) f a m i l y , a n d h o m o c y s t e i n e S-methyltransferase, displayed induced expression under drought stress (Kudapa et al, 2018). Likewise, RNA-seq analysis of various vegetative and reproductive tissues subjected to heat stress identified several important candidate genes, viz.…”
Section: Functional Genomic Resources For Drought and Heat Stress Tolmentioning
confidence: 99%
See 1 more Smart Citation
“…Thousands of differentially expressed genes (DEGs) emanating from gene expression experiments still remain inadequate to explain translation of genome sequence information into plant phenotypes (Kudapa et al 2018). To bridge this gap, Cicer arietinum gene expression atlas (CaGEA) was constructed from deep sequencing of 27 samples from five developmental stages (germination and seedling, vegetative, reproductive, and senescence) of the drought tolerant chickpea ICC 4958.…”
Section: Compressive Transcriptome Assemblies and Gene Expression Atlasmentioning
confidence: 99%